THE EFFECT OF APPLYING GROUP INVESTIGATION METHOD ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Rasta Elisa Girsang (TRANSFORM : Journal of English Language Teaching and Learning, 2014)
Abstract This study was conducted as an attempt to discover the effect of applying Group Investigation Method on students’ achievement in reading comprehension. It was an experimental research. The subject was students of Grade X, Senior High School Singosari (SekolahMenengahAtas: SMA), which consisted of 60 students. The research was divided into two groups: experimental and control groups. The instrument used to collect the data was reading test. To obtain the reliability of the test, the writer applied Kuder Richardson 21 formula. The result of the reliability was 0.77, and it was found that the test was reliable. The data were analyzed by using t-test formula. The analysis showed that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group at the level of significant = 0.05 with the degree of freedom (df) 58, t-observed value 4.26 > t-table value 2.00. The findings indicate that applying Group Investigation Method significantly affected the students’ achievement in reading comprehension. So, English teachers are suggested to use Group Investigation Method in order to improve students’ achievement in reading comprehension. Keywords: GI (Group Investigation Method), Students’ Reading Achievement, Reading Comprehension, Experimental Design, Reading Test